(untitled) (Palimpsesto, 2023)
Given the high competitiveness in the labor market, commercial companies are looking for professionals endowed with skills that allow them to carry out their activities responsibly to achieve productivity and sustainable development. An educational proposal is presented to obtain professional skills from experience, through the implementation of extramural educational processes for those who aspire to carry out corporate activities in Venezuela. The objective is to identify the competences and transversal axes involved in professional training in social sciences and corporate law, incorporating business spaces, with the use of educational resources that allow influencing the changes of operability towards a socially responsible economic development, highlighting sustainability as a transversal axis of the competencies of leadership, autonomy, critical thinking, conflict resolution and management of information technology, allowing the professional to be a multiplier of knowledge and generator of changes towards good organizational management.